Identification of a Gammaherpesvirus Selective Chemokine Binding Protein That Inhibits Chemokine Action - van Berkel, Victor (American Society for Microbiology, 2000)
Chemokines are involved in recruitment and activation of hematopoietic cells at sites of infection and inflammation. The M3 gene of γHV68, a gamma-2 herpesvirus that infects and establishes a lifelong latent infection and chronic vasculitis in mice, encodes an abundant secreted protein during productive infection. The M3 gene is located in a region of the genome that is transcribed during latency. We report here that the M3 protein is a high-affinity broad-spectrum chemokine scavenger. The M3 protein bound the CC chemokines human regulated upon activation of normal T-cell expressed and secreted (RANTES), murine macrophage inflammatory protein 1α (MIP-1α), and murine monocyte chemoattractant protein 1 (MCP-1), as well as the human CXC chemokine interleukin-8, the murine C chemokine lymphotactin, and the murine CX(3)C chemokine fractalkine with high affinity (K(d) = 1.6 to 18.7 nM). M3 protein chemokine binding was selective, since the protein did not bind seven other CXC chemokines (K(d) > 1 μM). Furthermore, the M3 protein abolished calcium signaling in response to murine MIP-1α and murine MCP-1 and not to murine KC or human stromal cell-derived factor 1 (SDF-1), consistent with the binding data. The M3 protein was also capable of blocking the function of human CC and CXC chemokines, indicating the potential for therapeutic applications. Since the M3 protein lacks homology to known chemokines, chemokine receptors, or chemokine binding proteins, these studies suggest a novel herpesvirus mechanism of immune evasion.